Chicken collagen hydrolysate cryoprotection of natural actomyosin: Mechanism studies during freeze-thaw cycles and simulated digestion. (15th November 2016) - Du, Lihui; Betti, Mirko
Highlights: Chicken collagen hydrolysate (CCH) can reduce actomyosin freeze-denaturation. The mechanism was related to its ice-inhibitive activity. CCH treatments caused less actomyosin unfolding and oxidation during freezing. Functionalities of frozen actomyosin were improved with CCH incorporations. Better elastic gels with higher digestibility were formed with CCH additions. Abstract: The cryoprotective effect of chicken collagen hydrolysate (CCH) obtained from chicken skin was investigated at 0%, 4%, 8% and 12% (w/w) on natural actomyosin (NAM) model system to elucidate the possible mechanism. Ice dimensions in the NAM dispersions were measured after 7 thermal cycles (stabilized at −20 °C and cycled between −16 °C to −12 °C) using a polarized microscope, demonstrating a significant reduction of ice crystal size induced by CCH. To determine the ice-controlling effect of CCH on protein freeze-denaturation, NAM samples were subjected to 7 freeze-thaw cycles between −20 °C and 4 °C. The results suggest that the presence of CCH can inhibit the ice crystals growth in NAM to reduce protein freeze-denaturation and oxidation similarly to the commercial cryoprotectants, resulting in higher protein solubility and a better gel structure with higher digestibility after freeze-thaw cycles.